2008
DOI: 10.1016/j.laa.2007.07.007
|View full text |Cite
|
Sign up to set email alerts
|

On the finiteness property for rational matrices

Abstract: We analyze the periodicity of optimal long products of matrices. A set of matrices is said to have the finiteness property if the maximal rate of growth of long products of matrices taken from the set can be obtained by a periodic product. It was conjectured a decade ago that all finite sets of real matrices have the finiteness property. This conjecture, known as the "finiteness conjecture", is now known to be false but no explicit counterexample to the conjecture is available and in particular it is unclear i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Finally, in the recent paper [GCCZ], we have proved that every pair of 2 × 2 binary sign-matrices, that is, with entries in {−1, 0, 1}, has the finiteness property. This supports the conjecture by Blondel and Jüngers [JB08] that this holds in general for all pairs of sign-matrices of any dimension. In turn, this fact would have the consequence that the finiteness property holds true for all families of rational matrices.…”
Section: Proposition 36 Let the Finite Family F Of Real N×n-matricesupporting
confidence: 90%
“…Finally, in the recent paper [GCCZ], we have proved that every pair of 2 × 2 binary sign-matrices, that is, with entries in {−1, 0, 1}, has the finiteness property. This supports the conjecture by Blondel and Jüngers [JB08] that this holds in general for all pairs of sign-matrices of any dimension. In turn, this fact would have the consequence that the finiteness property holds true for all families of rational matrices.…”
Section: Proposition 36 Let the Finite Family F Of Real N×n-matricesupporting
confidence: 90%
“…In [23] it was demonstrated that the finiteness conjecture is valid for any pair of 2 × 2 binary matrices, i.e. matrices with the elements {0, 1}, and in [24] a similar result was proved for any pair of 2 × 2 sign-matrices, i.e.…”
Section: Introductionmentioning
confidence: 81%
“…, } such that ρ(A i1 · · · A in ) = (A) n ? This question was answered negatively in 2002 by Bousch and Mairesse [13], but continues to stimulate research [7,14,26,31,35,40].…”
Section: Applications To the Study Of The 1-ratio Of Pairs Of Matricesmentioning
confidence: 99%